Desain dan Optimasi Antena Pita Lebar Planar Monopole Bentuk Sembarang dengan Algoritma Genetika dan Metoda Momen - Joko Suryana (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2018)
This paper presents a new approach in designing an ultra wideband minimum dispersion antenna optimally to avoid the degradation of broadband communications system performance. Design and iterative optimization are applied to an arbitrary shape of planar monopole antenna using a genetic algorithm combined with the moment method, abbreviated as AGMM method, and implemented with Matlab. Two arbitrary shapes of planar monopole antennas have been implemented in compact physical size using AGMM optimization, each having 9.1 GHz and 7.4 GHz bandwidths, the lowest frequency of 1.9 GHz and 2.7 GHz and fidelity 0.6 and 0.64 for any arbitrary discrete antenna and edge profile antenna. This method can be applied to design any arbitrary shapes of an ultra-wideband antenna with each has wide bandwidth more than 7 GHz, the lowest frequency below 3 GHz and a minimum fidelity of 0,55 that is suitable for high- speed communication, such as 5G system.